Editorial - Athanasopoulou, P.; Loureiro, S. M. C. (International Journal of Internet Marketing and Advertising, 2021)
Social media (SM) is defined as “a group of internet-based applications that build on the ideological and technological foundations of Web 2.0, and that allow the creation and exchange of user generated content” [Kaplan and Haenlein, (2010), p.61]. SM are increasingly used globally, and the number of users is expected to surpass 4.4 billion people in 2025 (Statista.com, 2021). Facebook has the highest number of users globally, around 2.7 billion monthly active users whereas Instagram comes second with 1 billion monthly active accounts (Statista.com, 2021).